(x+2y)and(2x-3y)=

Simple and best practice solution for (x+2y)and(2x-3y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2y)and(2x-3y)= equation:


Simplifying
(x + 2y) * and(2x + -3y) = 0

Reorder the terms for easier multiplication:
adn(x + 2y)(2x + -3y) = 0

Multiply (x + 2y) * (2x + -3y)
adn(x(2x + -3y) + 2y * (2x + -3y)) = 0
adn((2x * x + -3y * x) + 2y * (2x + -3y)) = 0

Reorder the terms:
adn((-3xy + 2x2) + 2y * (2x + -3y)) = 0
adn((-3xy + 2x2) + 2y * (2x + -3y)) = 0
adn(-3xy + 2x2 + (2x * 2y + -3y * 2y)) = 0
adn(-3xy + 2x2 + (4xy + -6y2)) = 0

Reorder the terms:
adn(-3xy + 4xy + 2x2 + -6y2) = 0

Combine like terms: -3xy + 4xy = 1xy
adn(1xy + 2x2 + -6y2) = 0
(1xy * adn + 2x2 * adn + -6y2 * adn) = 0
(1adnxy + 2adnx2 + -6adny2) = 0

Solving
1adnxy + 2adnx2 + -6adny2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'adn'.
adn(xy + 2x2 + -6y2) = 0

Factor a trinomial.
adn((2x + -3y)(x + 2y)) = 0

Subproblem 1

Set the factor 'adn' equal to zero and attempt to solve: Simplifying adn = 0 Solving adn = 0 Move all terms containing a to the left, all other terms to the right. Simplifying adn = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(2x + -3y)' equal to zero and attempt to solve: Simplifying 2x + -3y = 0 Solving 2x + -3y = 0 Move all terms containing a to the left, all other terms to the right. Add '-2x' to each side of the equation. 2x + -2x + -3y = 0 + -2x Combine like terms: 2x + -2x = 0 0 + -3y = 0 + -2x -3y = 0 + -2x Remove the zero: -3y = -2x Add '3y' to each side of the equation. -3y + 3y = -2x + 3y Combine like terms: -3y + 3y = 0 0 = -2x + 3y Simplifying 0 = -2x + 3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 3

Set the factor '(x + 2y)' equal to zero and attempt to solve: Simplifying x + 2y = 0 Solving x + 2y = 0 Move all terms containing a to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + 2y = 0 + -1x Combine like terms: x + -1x = 0 0 + 2y = 0 + -1x 2y = 0 + -1x Remove the zero: 2y = -1x Add '-2y' to each side of the equation. 2y + -2y = -1x + -2y Combine like terms: 2y + -2y = 0 0 = -1x + -2y Simplifying 0 = -1x + -2y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3X-3.9=-4.1 | | (x+5)(y-6000)=600000 | | 24=6*(x-7) | | logx^2=5 | | 2x^2+34x+17=0 | | 12n+9=6 | | (x+3)(x+4)+(x+6)(x-3)= | | 19=-(5x+7) | | 4(y-7)=5-(6y-2) | | C=39.45+0.25x | | 8z=3 | | 7(4x+2)=42 | | X^2-4x=5x | | 2.5k+5-1.5.5k=14 | | x^2+2x-363=0 | | 4x-8=7+3 | | v=Ixt | | z^3-z^2-6=0 | | 3y=0.006 | | 6=10c | | 1-5x=x-13 | | Log(x+4)=8 | | (2x)=1 | | Y-(-12)=7 | | 12x-6=-11x | | x^2-18x=1.25 | | 4(5x-8)-3(2x-7)= | | 9(9x)=96x | | 8x=(3x^2)-2 | | 7x-3=4x-24 | | (6f-k)= | | 36m^6+12m^4=m^2+0 |

Equations solver categories